Single-Sensor Hand Geometry And Palmprint Verification System - Goh, Michael Kah Ong (2004)
We propose a novel salient point detection algorithm to detect the crucial features of the hand for hand geometry measurement. These points are located on the tips and roots between two fingers. The proposed algorithm does not reguire any guidance material to fix the position of the user's hand. We developed a flexible and adjustable feature extractor for proposed system. The number of features extracted from the hand can be adjusted to suit the level of security desired by the application.